Chinese students’ selection of cross-border cooperative universities for tertiary education: intrinsic and extrinsic motivations - Huaqing He (Higher Education Evaluation and Development)
Purpose – This study aims to investigate and identify key motivations behind Chinese students’ decisions to enroll in a bachelor’s degree program at a cross-border cooperative university (CBCU). Design/methodology/approach – Semi-structured interviews were conducted with 12 undergraduate students who are currently enrolled in a cross-border cooperative university (CBCU). The data were analyzed based on the intrinsic and extrinsic motivation framework of Self-Determination Theory (SDT). Findings – Two primary motivations were identified: intrinsic motivations, including the desire for new experiences, quality educational resources, broader horizons and institutional support; and extrinsic motivations, such as constraints from Gaokao scores, uncertainties from the National College Entrance Examination system and the institution’s reputation enhancing their academic credentials. Most students exhibit a combination of these motivations, which interact to influence their university choice, with variations based on individual profiles. Originality/value – By examining and understanding the motivations of Chinese students, this study provides insights for higher education institutions to enhance student-centered services and highlights the benefits of educational collaboration, offering guidance for policymakers and stakeholders involved in similar initiatives.